1980
DOI: 10.1212/wnl.30.8.882
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of CSF gamma‐globulin banding in presenile dementia

Abstract: An improved agarose gel electrophoretic technique was used to fractionate serum and cerebrospinal fluid (CSF) proteins in patients with presenile dementia. The CSF electrophoretic patterns demonstrated three abnormal bands in the gamma-globulin region in five out of eight of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1981
1981
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…multiple sclerosis [14], have been associated with the presence of oligoclonal bands in CSF using IEF followed by immunofixation. Protein bands, probably representing oligoclonal IgG production, were demonstrated in CSF sam ples from 5 unselected cases with presenile dementia [22]. No such changes could be demonstrated in our material.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…multiple sclerosis [14], have been associated with the presence of oligoclonal bands in CSF using IEF followed by immunofixation. Protein bands, probably representing oligoclonal IgG production, were demonstrated in CSF sam ples from 5 unselected cases with presenile dementia [22]. No such changes could be demonstrated in our material.…”
Section: Discussioncontrasting
confidence: 52%
“…No such changes could be demonstrated in our material. Oligoclonal IgG production by plasma cells in CSF might be initiated by an unspecific reaction to the tissue damage found in the late stages of dementia and this may provide an explana tion for the contrasting results reported by other workers in studies on demented pa tients [22].…”
Section: Discussionmentioning
confidence: 85%
“…Although the occurrence of CNS specific OCB in the CSF of patients with Alzheimer's disease was first reported in 1980 [16] this and subsequent reports have only evaluated relatively small numbers of patients [1,5,10] [3,4,7,8]. The presence of OCB in primary neurodegenerative dementia is generally considered to be a rarity such that their absence is supportive of diagnosis, specifically for example of probable AD [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that sub‐populations of AD patients are characterized by oligoclonal bands in CSF, indicating intra‐blood‐brain barrier IgG production. This would support hypotheses concerning the involvement of infectious agents or abnormalities of the immune system in the etiology of AD 115 , 116 . This contention, however, is not supported by results of either conventional electrophoresis, agarose isoelectric focussing, or two‐dimensional polyacrylamide gel electrophoresis, all of which failed to show oligoclonal banding in CSF of AD patients 111 , 117–119 .…”
Section: Amino Acids and Proteinsmentioning
confidence: 71%